The complete mitochondrial genome of a leaf roller, Eudemis lucina (Lepidoptera: Tortricidae). Issue 2 (3rd July 2019) - Zhuang, Jialiang; Li, Yongyan; Yang, Wenxu; Feng, Weixing; Cao, Mengfei; Yu, Haili
Abstract: The leaf roller, Eudemis lucina, is a potential pest of Quercus in East Asia. In this study, we described the complete mitochondrial genome of this species by high-throughput sequencing. The mitochondrial genome is found to be a circular molecule of 16, 056 bp in length, which consisted of 13 protein-coding genes (PCGs), 22 tRNA genes, 2 rRNA genes, and a non-coding control region (A + T-rich region). The A + T content is 80.5% for the whole mitogenome. All PCGs are initiated by ATN codons, except for COI which is initiated by the CGA codon. Eight PCGs use a typical stop codon of TAA, whereas the remaining PCGs use incomplete stop codon of T–– or TA–. The non-coding control region is 1013 bp and located between s-rRNA and Met-tRNA.